Characterization of bacteria from nest products of stingless bee, Heterotrigona itama (Cockerell, 1918) - Ngalimat, Mohamad Syazwan (2019)
Stingless bee, Heterotrigona itama nest products which are propolis, honey, and bee bread are rich in antimicrobial activities which particularly limit the development of microorganisms. Regardless of the antimicrobial activities, some bacteria still can survive in nest products. To date, little is known about the bacterial species (other than lactic acid bacteria) in the nest products of H. itama. Therefore, the aim of this study was to isolate and characterise bacterial species (other than lactic acid bacteria) in the H. itama propolis, bee bread, and honey. The nest products were aseptically collected from four geographical localities of Malaysia. Total plate count (TPC), bacterial identification, phenotypic profile, enzymatic, and antimicrobial activities were studied.